Carnival Steel Band, Trinidad, B.W.I. - (:unkn) unknown (Y. De Lima and Co, Trinidad, Port of Spain, B.W.I., 2009)
A couple men playing steel pans on the street at Carnival time. The steel pans used here as a musical instrument were made from old oil drums.
Colour: Coloured (Hand painted); Style: Landscape; Other: Bordered, Divided
Keywords: Postcards; Trinidad and Tobago; Steel drum (Musical instrument)--Trinidad and Tobago; Music--Trinidad and Tobago; Musical instruments--Trinidad and Tobago; Carnival--Trinidad and Tobago; Men--Trinidad and Tobago; Steelbands (Music)--Trinidad and Tobago